Laser biostimulation for improving seeds germinative capacity and seedlings growth of Prosopis laevigata and Jacaranda mimosifolia - Costilla-Hermosillo, María Guadalupe; Ortiz-Morales, Martín; Loza-Cornejo, Sofía; Frausto-Reyes, Claudio; Ali Metwally, Sami (Instituto de Ecología, A.C., 2019)
“Jacaranda” (Jacaranda mimosifolia) and "mezquite” (Prosopis laevigata) are timber species that generally present problems with regard to the germination of their seeds in natural conditions, since they have a very hard and impermeable cover. Different treatments have been applied to improve the germinative response of both species with unfavorable results. This study aimed to know the effect of the pre-sowing laser biostimulation on germination and seedlings growth of these species. The seeds were biostimulated with a He-Ne laser (632 nm, 10 mW). Considering three replications of 50 seeds for each species, five irradiation treatments were applied (30 s, 60 s, 90 s, 120 s, 150 s) and control. The results for mezquite demonstrated that the highest number of germinated seeds (96%) was obtained with the treatments 90 s and 150 s; in contrast, the control seeds showed a lower germination percentage (16%). Additionally, the 30 s treatment produced a positive effect on the growth of the root, and it was different (p < 0.05) to the remaining treatments and the control. For Jacaranda, there were significant statistical differences (p < 0.05) between the control and the different treatments. 29% of seed germination occurs without any treatment. However, for 90 s and 120 s, germination is induced in a relatively high percent (97%-99%). For both species, the best treatment was 120 s, since higher values were recorded for all the morphological variables. It is concluded that laser biostimulation can produce beneficial effects on the germination of seeds and seedling growth and it could contribute to the propagation and conservation of these species.